Hypertension Analysis of stress Reduction using Mindfulness meditatiON and Yoga (The HARMONY Study): study protocol of a randomised control trial. Issue 2 (5th March 2012) - Blom, Kimberly; How, Maxine; Dai, Monica; Baker, Brian; Irvine, Jane; Abbey, Susan; Abramson, Beth L; Myers, Martin; Perkins, Nancy; Tobe, Sheldon W
Abstract : Introduction: Hypertension (HTN) is a leading risk factor for preventable cardiovascular disease, with over one in five adults affected worldwide. Lifestyle modification is a key strategy for the prevention and treatment of HTN. Stress has been associated with greater cardiovascular risk, and stress management is a recommended intervention for hypertensives. Stress reduction through relaxation therapies has been shown to have an effect on human physiology, including lowering blood pressure (BP). However, individualised behavioural interventions are resource intensive, and group stress management approaches have not been validated for reducing HTN. The HARMONY Study is a pilot randomised controlled trial designed to determine if mindfulness-based stress reduction (MBSR), a standardised group therapy, is an effective intervention for lowering BP in stage 1 unmedicated hypertensives. Methods and analysis: Men and women unmedicated for HTN with mean daytime ambulatory blood pressure (ABP) ≥135/85 mm Hg or 24 h ABP ≥130/80 mm Hg are included in the study. Subjects are randomised to receive MBSR immediately or after a wait-list control period. The primary outcome measure is mean awake and 24 h ABP. The primary objective of the HARMONY Study is to compare ABP between the treatment and wait-list control arm at the 12-week primary assessment period. Results from this study will determine if MBSR is an effective intervention for lowering BP in early unmedicated hypertensives. Ethics and dissemination: This research project was approved by the Sunnybrook Research Ethics Board and the University Health Network Research Ethics Board (Toronto, Canada). Planned analyses are in full compliance with the principles of the Declaration of Helsinki. Data collection will be completed by early spring 2012. Primary and secondary analysis will commence immediately after data monitoring is completed; dissemination plans include preparing publications for submission during the summer of 2012. Trial registration number: This study is registered with http://clinicaltrials.gov (NCT00825526 ).